Hereditary Consumption of Herbs and Marketing Communication influence in Nigeria and Zambia - Mercy BANDA; Oscar ODIBOH (Communications of International Proceedings, 2020)
Consumption of herbs is increasing in various parts of the world. However, in many African countries, public perception of hereditary consumption of herbs is yet unclear especially as regards to marketing communication. In Nigeria and Zambia for example, tradition, religion, level of education, economy, healthcare needs and other factors influence hereditary consumption in general terms. Nonetheless, misconceptions still surround the hereditary consumption of herbs specifically relating to marketing communication activities. Quantitative survey design using the questionnaire instrument was deployed. Two hundred and twenty-three out of 230 copies of the questionnaire successfully returned from respondents who were selected through a multi-stage sampling technique. Tentative findings show that hereditary consumption and marketing communication have less than average influence on the uptake of herbs by Nigerians and Zambians. Local and global stakeholders in African herbal medicine will find this study’s results beneficial for further investigation.
Keywords: Hereditary Consumption; Herbs; Marketing Communication; Nigeria; Zambia.